Prognostic Value of Measuring Handgrip Strength (HGS) for Stroke Patients - Shama Razzaq; Tahseen Kazmi; Amna Khalid; Jamal Abdul Nasir; Ahmed Saud; Saadia Shahzad (ziauddin University, 2024)
Background: A handgrip dynamometer is a simple, inexpensive and quick method to assess muscle strength. Sequential decrease in handgrip strength has been shown in various studies as a strong predictor of stroke. Therefore, this study aimed to measure muscular strength and determined its association with co-morbidities to predict critical illness in a community based setting of Punjab, Pakistan. Methods: The study participants (n=152), were recruited through convenient sampling, during a community-based survey. Muscle strength was assessed with the handgrip dynamometer and quantified according to high, average and low percentile. Chi-square test was done to assess the distribution and multinomial logistic regression analysis to identify the factors associated with them. Results: Out of 152 participants, mean age 44.5±15.3 years, 95(62.5%) were females and 57(35.5%) males. Handgrip strength measurement showed that 38(25%) of participants had high muscle strength, 80(52.6%) average and 34(22.4%) had low muscle strength. Low muscle strength was significantly higher among females (OR: 7.9, 95% CI: 2.4-27.1) as compared to the males. In general participants having diabetes had low muscle strength (p<0.011), but in hypertensive the association was not significant (p<0.21). Conclusion: Overall patients at risk of stroke such as diabetics had significant low muscle strength but in hypertensive the association was not significant (p<0.21). More studies with bigger sample size are required to make it a predictive marker for stroke and cardiovascular diseases. It is easy to measure and is a low-cost technique for risk scoring and risk prediction in a community-based setting at an early stage. Keywords: Muscles; Risk; Adult; Community.